Evolution of Stroke Thrombectomy Techniques to Optimize First-Pass Complete Reperfusion - Ospel, Johanna Maria (Semin Intervent Radiol, 2020)
Since 2015, endovascular therapy (EVT) has become the standard of care for acute ischemic stroke (AIS) due to large vessel occlusion. It is a safe and highly effective treatment, and its number needed to treat of 2.6 is one of the highest throughout medicine. The ultimate goal when performing EVT is to maximize chances of good outcome through achievement of fast first-pass complete reperfusion, as incomplete and delayed reperfusion increases complication rates and negatively affects outcome. Since EVT has been established as standard of care, new devices have been developed and treatment techniques have been refined. This review provides a brief overview about the rationale for and history of EVT, followed by a detailed step-by-step description of how to perform EVT using the BADDASS (BAlloon guide with large bore Distal access catheter with Dual Aspiration with Stent-retriever as Standard approach), a combined technique, which is in our opinion the safest and most effective way to achieve fast first-pass complete reperfusion. We also discuss treatment strategies for patients with simultaneous high-grade carotid stenosis/pseudoocclusion/occlusion and gaining carotid access in challenging arch anatomy, as these are commonly encountered situations in AIS, and conclude with an outlook on new technologies and future directions of EVT.